The Role of Companions in the Wirausaha Baru (WUB)Program of Depok City in 2023 - Atmowijoyo, Ummi; Rahayu, Ety (Jurnal Indonesia Sosial Sains, 2024)
The Wirausaha Baru (WUB) Program is a government program under the coordination of the Ministry of Cooperatives and Small and Medium Enterprises (UKM) whose implementation is handed over to the city-level government, in this case, the Department of Cooperatives & Micro Enterprises (DKUM). This program has been running since 2017 until now and continues to experience developments in implementation practices in the field. The Depok City Government is one of the city governments that has consistently implemented the Wirausaha Baru (WUB) Program. This empowerment program, which targets micro-business actors, focuses on capital aspects and includes training, mentoring, and providing infrastructure to develop businesses. Program participants selected will be given the proper entrepreneurial knowledge and the ability to grow their businesses through entrepreneurship education, business management, marketing access, access to financing, and product legality. Participants also receive assistance in capital, marketing, and business management. In mentoring activities, the Companion is one of the elements that has a significant role as a Change Agent / Actor of Change (Ife, 1997), In every program, it is always hoped that the Program Participants will achieve changes for the better according to the targets or goals of the program owner. This research analyzes mentoring activities in implementing the Depok City Wirausaha Baru (WUB) Program in 2023. This research approach is qualitative with a descriptive research type. In-depth interviews were conducted with Mentors at all levels, Program Participants, and Program Organizers, using purposive sampling techniques. The research results show that mentoring activities in the 2023 New City Entrepreneurship (WUB) program are running well and in accordance with what is regulated in Depok Mayor Regulation No. 20 of 2022 concerning Guidelines for Wirausaha Baru (WUB) Programs. The competencies obtained from the Companion Training/TOT and the mentoring work forms created by the Implementation Team help the Companion carry out their roles and functions as enablers, educators, advocates, brokers, and experts.